A method for preparing a dense antibacterial film based on bamboo with multi-component synergistic enhancement
By combining biological enzymes with chemical reagents to remove lignin from bamboo, and using a process of combining vacuum filtration and hot pressing, a multivariate and synergistically enhanced dense antibacterial film is prepared, which solves the strength and heat resistance of traditional plastics and bioplastics. The lack of properties and antibacterial properties has achieved efficient and environmentally friendly film preparation.
Patent Information
- Application Number
- CN202411027565.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-30
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-07-30
AI Technical Summary
The difficulty in degradation and high production costs of traditional plastics limit their use in certain applications, and bioplastics have shortcomings in strength, heat resistance and antibacterial properties.
The combination of biological enzymes and chemical reagents to remove lignin from bamboo, and a multivariate and synergistically enhanced dense antibacterial film was prepared through a process of combining vacuum filtration and hot pressing. It uses microcrystalline cellulose, lignin and nano-scale TiO2 and other materials. The synergistic effect of the film improves the mechanical strength, antibacterial properties and denseness.
Adhesive-free preparation is achieved, production costs and chemical reagents are reduced, and the mechanical strength, antibacterial properties and density of the film are improved. It is suitable for food packaging, biomedicine and other fields.
Smart Images

Figure CN118834418B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of preparing films by refining green biomass, and in particular relates to a method for preparing a dense antibacterial film based on bamboo material with multi-component synergistic enhancement. Background Art
[0002] In life, although the plastic industry has brought many conveniences and wide applications, it also has some significant disadvantages, including environmental pollution, toxicity problems, resource consumption and biodiversity impact. The difficulty of plastic degradation is an urgent problem to be solved, especially traditional plastics such as polyethylene (PE) and polypropylene (PP), which will exist in the natural environment for a long time and cause serious pollution, such as plastic waste accumulation and microplastic pollution. The accumulation of plastic waste will pose a threat to wildlife and ecosystems. Plastic waste in the ocean causes harm to marine life and the problem of plastic pollution in terrestrial ecosystems. Plastics are not only harmful to the environment and ecosystems, but also pose a potential threat to human health. Some plastic products contain harmful substances, such as phthalates (such as DEHP) and bisphenol A (BPA). In addition, the production of plastics requires non-renewable resources such as petroleum as raw materials. The production of plastics consumes a lot of resources and is dependent on the energy supply chain, which increases the pressure on limited resources to a certain extent. Therefore, bioplastics are regarded as a potential sustainable solution to replace traditional plastics due to their advantages.
[0003] Bioplastics are usually based on biodegradable raw materials, such as plant starch, cellulose, polylactic acid, etc. They can be decomposed into natural substances under certain conditions, reducing the long-term impact on the environment. These raw materials mainly come from renewable resources, such as bamboo, straw, corn, sugarcane, cassava and other plants. Compared with petroleum-based plastics, they reduce dependence on non-renewable resources and help reduce carbon footprint. In addition, compared with plastics, bioplastics usually do not contain harmful substances and do not pose a threat to human health. Despite these advantages, bioplastics also face some challenges: some bioplastics may not be as good as traditional plastics in terms of strength, heat resistance, aging resistance, etc., which limits their use in certain application areas; the production cost of bioplastics is usually high, especially when applied on a large scale, which may affect their market competitiveness; bioplastics mainly include the removal of hemicellulose, lignin, pectin, etc., the modification of natural fibers and the use of viscose technology, etc., which may cause environmentally harmful substances to be produced during the production process of bioplastics. If the chemical reagents used in the process are excessive and the recycling effect is not good, it will also cause environmental pollution problems.
[0004] Bamboo, as the raw material source of microcrystalline cellulose, is a very abundant and renewable resource. Compared with wood, bamboo has a shorter growth cycle and can be regenerated and utilized more quickly. The high cellulose content of bamboo ensures the extraction of microcrystalline cellulose (MCC), and the excellent chemical stability, thermal stability and biocompatibility of MCC have promoted its widespread adoption in different industries such as pharmaceuticals, food, and cosmetics. Studies have found that most of the current research focuses on the preparation of some bioplastic films using cellulose nanocrystals (CNC), and the research on MCC is relatively small. Compared with cellulose nanocrystals (CNC), MCC has the advantages of low industrial production cost, high efficiency, and good availability. The solvent system used in the extraction process of MCC is also more environmentally friendly than CNC. Therefore, it is a better solution to propose a new technical strategy, that is, to rationally prepare a multi-component synergistically enhanced composite film, which utilizes the characteristics and advantages of each component to achieve performance improvement of the film in multiple aspects.
[0005] Traditionally, one of the main methods for preparing wood-based recombinant materials from natural wood is by bonding plant fibers with adhesives. However, this process has many disadvantages, including high adhesive costs and formaldehyde release. Formaldehyde has a huge impact on human health and is a carcinogen. Therefore, in order to reduce the cost of adhesives, implement the concept of green sustainable development, and develop adhesive-free materials in line with the sustainable development direction of ecological environmental protection, that is, under hot pressing conditions, it can be prepared by self-bonding between plant fibers without any adhesive, and the presence and thermal softening of lignin in the fibers are closely related to the performance of bio-based materials. Therefore, it is a challenging problem to study the removal of lignin in wood and the microscopic mechanism in adhesive-free materials, and to use its characteristics to prepare wood-based recombinant materials with excellent performance. Summary of the invention
[0006] In view of the above-mentioned existing problems, in order to reduce the production cost of bioplastics and the amount of chemical reagents used, and to have strong mechanical strength without using adhesives, the present invention proposes a method for preparing a dense antibacterial film with multi-component synergistic enhancement based on bamboo, which uses a combination of biological enzymes and chemical reagents to remove lignin to prepare one of the raw materials of the dense antibacterial film, microcrystalline cellulose (MCC), with a small amount of pharmaceutical raw materials, and a multi-component synergistically enhanced dense antibacterial film prepared from four materials of MCC, lignin, titanium dioxide, and glycerol by a process combining vacuum filtration and hot pressing. The operation is simple, the performance is excellent, and the organization is compact. The present invention uses natural bamboo and can produce a dense antibacterial film that is synergistically enhanced through the interaction mechanism between the raw materials and the film forming method without using adhesives.
[0007] The above purpose is achieved through the following technical solutions:
[0008] The present invention first provides a method for preparing a dense antibacterial film based on bamboo with multi-element synergistic reinforcement, the method comprising the following steps:
[0009] S1. Processing natural bamboo strips into 120 mesh bamboo powder fiber powder, referred to as BFP, and then soaking it in sodium acetate buffer and then performing biological enzyme treatment, wherein the mass ratio of bamboo powder fiber powder to hemicellulase, laccase, and pectinase in the enzyme treatment is 100:1.5:2:1, the enzyme hydrolysis temperature is 45±5°C, and the enzyme hydrolysis time is 6±1h. After the treatment, the mixture is filtered, washed to neutrality, and dried to obtain the enzyme-treated powder, referred to as E-BFP;
[0010] S2. treating the powder obtained in step S1 with alkali and drying the filter residue to obtain an alkali-treated powder, referred to as A-BFP;
[0011] S3. The powder A-BFP obtained in step S2 is treated by a staged bleaching method from mild to strong, and finally subjected to ultrasonic treatment, washed with boiling deionized water until neutral and dried to obtain microcrystalline cellulose, referred to as MCC;
[0012] S4. Take the microcrystalline cellulose MCC obtained in step S3, add it into water to prepare a microcrystalline cellulose MCC dispersion with a mass percentage concentration of 1%, then add 10% lignin based on the mass of MCC and 5%-20% TiO2 based on the mass of MCC to the dispersion to obtain a mixed solution, stir the mixed solution at 90±5°C for 2h to obtain a MCC / LNP / TiO2 polymer solution, then add plasticizer glycerol (G) and stir at 90±5°C for 30min to obtain a MCC / LNP / TiO2 / G polymer solution; vacuum filter it to obtain a wet sheet, and hot-press the obtained wet sheet to obtain a composite film HP-MLTG.
[0013] Furthermore, in step S1, the natural bamboo strips are processed into 120-mesh bamboo powder fiber powder. The specific process is to cut the natural bamboo strips into short pieces and place them in a 60°C electric blast oven to dry until the quality no longer changes. After taking them out, they are crushed by a multifunctional high-speed crusher and sieved through a 120-mesh sieve to obtain a sieve-under product, 120-mesh bamboo powder fiber powder, referred to as BFP.
[0014] Furthermore, the immersion in the sodium acetate buffer in step S1 has a pH of 5.5 and a solid-liquid ratio (g:ml) of 1:20.
[0015] Furthermore, the alkali treatment in step S2 is to place the E-BFP powder obtained in step S1 in a 3% by mass NaOH solution for 4 hours, with the solid-liquid ratio set to 1:10 (g:ml), and the alkali treatment temperature being 80°C.
[0016] Furthermore, the staged bleaching method in step S3 is specifically that during the first bleaching, the ratio of the A-BFP powder obtained in step S2, sodium hydroxide, and 8wt.% hydrogen peroxide is 1:1:100 (g:g:ml), and the subsequent bleaching adopts the drying after the previous bleaching, sodium hydroxide, and 8wt.% hydrogen peroxide in a ratio of 1:1:150 (g:g:ml) until bleaching to white, and the staged bleaching method is carried out at 80±5°C.
[0017] Furthermore, the amount of the plasticizer glycerol (G) added in step S4 is 4% of the mass of the MCC / LNP / TiO2 polymer solution.
[0018] Furthermore, the hot pressing conditions in step S4 are: 100° C., 0.5 MPa in a hot press, and the hot pressing time is 40 min.
[0019] Furthermore, the method also includes a process of placing the composite film HP-MLTG obtained by hot pressing at 23° C. and 50% relative humidity to balance the moisture for 72 hours.
[0020] The invention also provides a bamboo-based multi-component synergistically reinforced dense antibacterial film prepared by the method.
[0021] Beneficial effects:
[0022] 1. Currently, nanocellulose is mainly used to prepare films. The research on nanocellulose films is more extensive and in-depth than that on microcrystalline cellulose films. In view of the fact that microcrystalline cellulose has a larger fiber diameter and thicker fiber bundles, it usually has a higher thermal stability than nanocellulose; the process for preparing microcrystalline cellulose is simpler, the raw materials are easier to obtain, and the cost of microcrystalline cellulose is usually lower than that of nanocellulose; and in the preparation process, it usually does not require precise processing and control conditions like nanocellulose, which reduces the preparation cost and improves the preparation efficiency, especially in large-scale production. Therefore, the present invention uses microcrystalline cellulose extracted from natural bamboo by a biological enzyme combined with a NaOH-based water system as a raw material and an environmentally friendly and economical method.
[0023] 2. In addition to the relatively weak research on microcrystalline cellulose films, the environmentally friendly adhesives used in the existing film preparation include starch, gelatin, etc., which replace traditional adhesives such as phenolic resins and urea-formaldehyde resins that release formaldehyde. However, films made of starch, gelatin, etc. as one of the raw materials will have some shortcomings, such as: starch film has poor resistance to oxygen, which easily leads to oxidation and deterioration of the packaged food; gelatin is easily dissolved in high-temperature water, which may cause inconvenience or be unsuitable for use in the production and packaging of certain foods. Therefore, the present invention proposes to use lignin as an adhesive, and utilize the inherent binding ability and hydrogen bond network of lignin to promote fiber self-bonding. A composite film with good performance can be prepared without the need to add additional adhesives. Lignin can also combine with the active hydroxyl groups in the plasticizer glycerol through its abundant phenolic hydroxyl groups, thereby improving the performance of the film.
[0024] 3. When it comes to food packaging, biomedicine and other fields, the antibacterial properties of the film are generally considered to be crucial. However, the antibacterial capabilities of pure cellulose, microcrystalline cellulose and lignin are very limited, which seriously limits their wide application in these fields. Therefore, the present invention uses nano-TiO2 as an inorganic antibacterial material, because nano-TiO2 has photocatalytic antibacterial activity. When TiO2 is activated by ultraviolet (UV) or visible light, photogenerated electrons and photogenerated holes are generated. The photogenerated electrons react with oxygen to generate superoxide anions, while the photogenerated holes react with water molecules or hydroxide ions to generate hydroxyl free radicals, which can destroy the biofilm of bacteria, thereby exerting an antibacterial effect.
[0025] 4. The commonly used methods for preparing thin films are mainly vacuum filtration, solution casting and hot pressing. Among them, the vacuum filtration method is relatively simple to operate, and the equipment and operation costs are relatively low, but the filtration effect is limited by the pore size and thickness of the filter paper used, which leads to the densification effect of the film; although the solution casting method is simple to operate and the thickness and surface morphology of the film can be controlled by adjusting the solution concentration and casting speed, the drying process of the solution casting is relatively slow and the preparation cycle is long; the hot pressing method is fast in preparing thin films and is suitable for large-scale and high-yield production needs. It can also make the material molecules more closely arranged and improve the density and mechanical properties of the film, but it is more complicated and difficult to operate for materials with weak adhesion, so hot pressing is not suitable for all types of materials. The present invention proposes to combine the vacuum filtration method with the hot pressing method to prepare the film and shape it. The vacuum filtration method effectively regulates the pore structure and component distribution of the film, improves the uniformity and purity of the film, and reduces the void and gas content. Then, the obtained wet film is hot pressed to make the components more tightly combined in the film, enhance its mechanical properties and durability, and help form a dense surface structure and excellent surface flatness, which is suitable for polymer solutions with weak adhesion. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a planar microscopic morphology (SEM) image of the film prepared in the present invention. Figure 1 In the figure, a is a plan microscopic morphology (SEM) image of the film prepared in Example 1, b is a plan microscopic morphology (SEM) image of the film prepared in Example 2, c is a plan microscopic morphology (SEM) image of the film prepared in Example 3, and d is a plan microscopic morphology (SEM) image of the film prepared in Example 4;
[0027] Figure 2 This is a cross-sectional microscopic morphology (SEM) image of the film prepared in the present invention. Figure 2 In the figure, a is a cross-sectional microscopic morphology (SEM) image of the film prepared in Example 1, b is a cross-sectional microscopic morphology (SEM) image of the film prepared in Example 2, c is a cross-sectional microscopic morphology (SEM) image of the film prepared in Example 3, and d is a cross-sectional microscopic morphology (SEM) image of the film prepared in Example 4;
[0028] Figure 3 This is the thermogravimetric analysis (TGA) graph of the film prepared in the present invention. DETAILED DESCRIPTION
[0029] The invention is further described below in conjunction with specific embodiments.
[0030] Embodiment 1:
[0031] S1. Bioenzyme treatment: Cut natural bamboo strips into short pieces and place them in an electric blast oven at 60°C to dry until the mass no longer changes. After taking them out, they are crushed by a multifunctional high-speed pulverizer and sieved through a 120-mesh sieve to obtain bamboo fiber powder (BFP); the dried bamboo fiber powder (BFP) is mixed with sodium acetate buffer at pH 5.5 at a solid-liquid ratio of 1:20 (g:ml) in a beaker and soaked for 2 hours before bioenzyme treatment, wherein the mass ratio of bamboo powder fiber powder to hemicellulase, laccase, and pectinase in the enzyme treatment is 100:1.5:2:1, the enzyme hydrolysis temperature is 45°C, and the enzyme hydrolysis time is 6 hours. After the hydrolysis, the mixture is filtered, washed to neutrality, and dried to obtain the enzyme-treated powder (E-BFP).
[0032] S2. Alkali treatment: The powder (E-BFP) obtained in step (1) is placed in a 3% by mass NaOH solution for treatment for 4 hours, wherein the solid-liquid ratio is set to 1:10 (g:ml), the alkali treatment temperature is 80°C, and the filter residue obtained after the NaOH treatment is dried to obtain the alkali-treated powder (A-BFP).
[0033] S3. Stepwise bleaching: Repeatedly bleach with hydrogen peroxide in an alkaline environment at 80°C until white, and treat the powder (A-BFP) obtained in step (2) by stepwise bleaching from mild to strong. The ratio of the dried powder (A-BFP), sodium hydroxide, and 8wt.% hydrogen peroxide in the first bleaching is 1:1:100 (g:g:ml), and the subsequent bleaching uses the dried powder (A-BFP) after the previous bleaching, sodium hydroxide, and 8wt.% hydrogen peroxide in a ratio of 1:1:150 (g:g:ml), until the remaining material is bleached to white, and then ultrasonically treated, washed with boiling deionized water until neutral and dried to obtain microcrystalline cellulose (MCC).
[0034] S4. Film preparation: Weigh 1% of microcrystalline cellulose (MCC), lignin (LNP) (10% based on the mass of MCC), and TiO2 (5% based on the mass of MCC), put them into water and stir the mixed solution at 90°C for 2h to obtain MCC / LNP / TiO2 polymer solution, then add plasticizer glycerol (G) (4% of the solution) and stir at 90°C for 30min to obtain MCC / LNP / TiO2 / G polymer solution; pour it into a Buchner funnel for vacuum filtration to obtain a thin wet sheet, and put the obtained wet sheet into a hot press at 100°C and 0.5MPa for 40min. The composite film (HP-MLTG) obtained after hot pressing is placed at 23°C and 50% relative humidity to balance the moisture for 72 hours.
[0035] Embodiment 2:
[0036] Bioenzyme treatment: natural bamboo strips are cut into short pieces and placed in a 60°C electric blast oven to dry until the mass no longer changes. After being taken out, they are crushed by a multifunctional high-speed pulverizer and sieved through a 120-mesh sieve to obtain bamboo fiber powder (BFP); the dried bamboo fiber powder (BFP) is mixed with sodium acetate buffer of pH 5.5 at a solid-liquid ratio (g:ml) of 1:20 in a beaker and soaked for 2 hours before bioenzyme treatment, wherein the mass ratio of bamboo powder fiber powder to hemicellulase, laccase, and pectinase in the enzyme treatment is 100:1.5:2:1, the enzyme hydrolysis temperature is 45°C, and the enzyme hydrolysis time is 6 hours. After the hydrolysis, the mixture is filtered, washed to neutrality, and dried to obtain the enzyme-treated powder (E-BFP).
[0037] Alkali treatment: The powder (E-BFP) obtained in step (1) was placed in a 3% NaOH solution for 4 h, wherein the solid-liquid ratio was set to 1:10 (g:ml), and the alkali treatment temperature was 80°C. The filter residue obtained after the NaOH treatment was dried to obtain the alkali-treated powder (A-BFP).
[0038] Stepwise bleaching treatment: Repeatedly bleach with hydrogen peroxide in an alkaline environment at 80°C until white, and treat the powder (A-BFP) obtained in step (2) by stepwise bleaching from mild to strong. The ratio of the dried powder (A-BFP), sodium hydroxide, and 8wt.% hydrogen peroxide in the first bleaching is 1:1:100 (g:g:ml), and the subsequent bleaching uses the dried powder (A-BFP) after the previous bleaching, sodium hydroxide, and 8wt.% hydrogen peroxide in a ratio of 1:1:150 (g:g:ml), until the remaining material is bleached to white, and then ultrasonically treated, washed with boiling deionized water until neutral and dried to obtain microcrystalline cellulose (MCC).
[0039] Film preparation: Weigh 1% microcrystalline cellulose (MCC), lignin (LNP) (10% based on the mass of MCC), and TiO2 (10% based on the mass of MCC), put them into water and stir the mixed solution at 90°C for 2h to obtain MCC / LNP / TiO2 polymer solution, then add plasticizer glycerol (G) (4% of the solution) and stir at 90°C for 30min to obtain MCC / LNP / TiO2 / G polymer solution; pour it into a Buchner funnel for vacuum filtration to obtain a thin wet sheet, and put the obtained wet sheet into a hot press at 100°C and 0.5MPa for 40min. The composite film (HP-MLTG) obtained after hot pressing is placed at 23°C and 50% relative humidity to balance the moisture for 72 hours.
[0040] Embodiment 3:
[0041] Bioenzyme treatment: natural bamboo strips are cut into short pieces and placed in a 60°C electric blast oven to dry until the mass no longer changes. After being taken out, they are crushed by a multifunctional high-speed pulverizer and sieved through a 120-mesh sieve to obtain bamboo fiber powder (BFP); the dried bamboo fiber powder (BFP) is mixed with sodium acetate buffer of pH 5.5 at a solid-liquid ratio (g:ml) of 1:20 in a beaker and soaked for 2 hours before bioenzyme treatment, wherein the mass ratio of bamboo powder fiber powder to hemicellulase, laccase, and pectinase in the enzyme treatment is 100:1.5:2:1, the enzyme hydrolysis temperature is 45°C, and the enzyme hydrolysis time is 6 hours. After the hydrolysis, the mixture is filtered, washed to neutrality, and dried to obtain the enzyme-treated powder (E-BFP).
[0042] Alkali treatment: The powder (E-BFP) obtained in step (1) was placed in a 3% NaOH solution for 4 h, wherein the solid-liquid ratio was set to 1:10 (g:ml), and the alkali treatment temperature was 80°C. The filter residue obtained after the NaOH treatment was dried to obtain the alkali-treated powder (A-BFP).
[0043] Stepwise bleaching treatment: Repeatedly bleach with hydrogen peroxide in an alkaline environment at 80°C until white, and treat the powder (A-BFP) obtained in step (2) by stepwise bleaching from mild to strong. The ratio of the dried powder (A-BFP), sodium hydroxide, and 8wt.% hydrogen peroxide in the first bleaching is 1:1:100 (g:g:ml), and the subsequent bleaching uses the dried powder (A-BFP) after the previous bleaching, sodium hydroxide, and 8wt.% hydrogen peroxide in a ratio of 1:1:150 (g:g:ml), until the remaining material is bleached to white, and then ultrasonically treated, washed with boiling deionized water until neutral and dried to obtain microcrystalline cellulose (MCC).
[0044] Film preparation: Weigh 1% microcrystalline cellulose (MCC), lignin (LNP) (10% based on the mass of MCC), and TiO2 (15% based on the mass of MCC), put them into water and stir the mixed solution at 90°C for 2h to obtain MCC / LNP / TiO2 polymer solution, then add plasticizer glycerol (G) (4% of the solution) and stir at 90°C for 30min to obtain MCC / LNP / TiO2 / G polymer solution; pour it into a Buchner funnel for vacuum filtration to obtain a thin wet sheet, and put the obtained wet sheet into a hot press at 100°C and 0.5MPa for 40min. The composite film (HP-MLTG) obtained after hot pressing is placed at 23°C and 50% relative humidity to balance the moisture for 72 hours.
[0045] Embodiment 4:
[0046] Bioenzyme treatment: natural bamboo strips are cut into short pieces and placed in an electric blast oven at 60°C to dry until the mass no longer changes. After being taken out, they are crushed by a multifunctional high-speed pulverizer and sieved through a 120-mesh sieve to obtain bamboo fiber powder (BFP); the dried bamboo fiber powder (BFP) is mixed with sodium acetate buffer of pH 5.5 at a solid-liquid ratio (g:ml) of 1:20 in a beaker and soaked for 2 hours before bioenzyme treatment, wherein the mass ratio of bamboo powder fiber powder to hemicellulase, laccase, and pectinase in the enzyme treatment is 100:1.5:2:1, the enzyme hydrolysis temperature is 45°C, and the enzyme hydrolysis time is 6 hours. After the hydrolysis, the mixture is filtered, washed to neutrality, and dried to obtain the enzyme-treated powder (E-BFP).
[0047] Alkali treatment: The powder (E-BFP) obtained in step (1) was placed in a 3% NaOH solution for 4 h, wherein the solid-liquid ratio was set to 1:10 (g:ml), and the alkali treatment temperature was 80°C. The filter residue obtained after the NaOH treatment was dried to obtain the alkali-treated powder (A-BFP).
[0048] Stepwise bleaching treatment: Repeatedly bleach with hydrogen peroxide in an alkaline environment at 80°C until white, and treat the powder (A-BFP) obtained in step (2) by stepwise bleaching from mild to strong. The ratio of the dried powder (A-BFP), sodium hydroxide, and 8wt.% hydrogen peroxide in the first bleaching is 1:1:100 (g:g:ml), and the subsequent bleaching uses the dried powder (A-BFP) after the previous bleaching, sodium hydroxide, and 8wt.% hydrogen peroxide in a ratio of 1:1:150 (g:g:ml), until the remaining material is bleached to white, and then ultrasonically treated, washed with boiling deionized water until neutral and dried to obtain microcrystalline cellulose (MCC).
[0049] Film preparation: Weigh 1% microcrystalline cellulose (MCC), lignin (LNP) (10% based on the mass of MCC), and TiO2 (20% based on the mass of MCC), put them into water and stir the mixed solution at 90°C for 2h to obtain MCC / LNP / TiO2 polymer solution, then add plasticizer glycerol (G) (4% of the solution) and stir at 90°C for 30min to obtain MCC / LNP / TiO2 / G polymer solution; pour it into a Buchner funnel for vacuum filtration to obtain a thin wet sheet, and put the obtained wet sheet into a hot press at 100°C and 0.5MPa for 40min. The composite film (HP-MLTG) obtained after hot pressing is placed at 23°C and 50% relative humidity to balance the moisture for 72 hours.
[0050] Table 1 shows the thickness, tensile strength and elongation at break of the films (HP-MLTG) prepared in Examples 1 to 4:
[0051] sample Sample thickness (mm) Tensile strength(MPa) Elongation after break (%) Example 1 0.44 16.00 6.74% Example 2 0.45 24.64 6.83% Example 3 0.46 34.34 6.85% Example 4 0.47 12.31 6.53%
[0052] As shown in Table 1, the elongation at break does not change significantly with the change of TIO2 content, but the tensile strength varies greatly. When the TIO2 content is 15%, the tensile strength of the film is the highest, which is 34.34MPa. This is because hydrogen bonds are formed between MCC, lignin and glycerol molecules. When the TIO2 content is 15%, the degree of bonding between molecules is the highest, thus strengthening the tensile strength of the film.
[0053] The planar microscopic morphology (SEM) of the film is shown in Figure 1 As shown in the figure, it can be seen that the fiber arrangement of the film after vacuum filtration and hot pressing is more orderly, the structure is compact, and there are fewer micro-hole defects. White spots, namely titanium dioxide, can be observed on the surface. As the content of titanium dioxide increases, the white spots become denser, but they are not obviously agglomerated together, which shows that all components in the nanocomposite material have good compatibility.
[0054] The cross-sectional microscopic morphology (SEM) of the film is shown in Figure 2 As shown in the figure, it can be seen that the cross-section of the film after vacuum filtration and hot pressing has a tight structure, less stratification, and a strong structural density, indicating that the method of combining vacuum filtration and hot pressing is effective.
[0055] The thermogravimetric analysis (TGA) curve of the film is shown in Figure 3 As shown, the curve exhibits three main stages of thermal degradation. In all composite films, the initial degradation up to 110°C showed a loss of about 3%-10% of the actual weight, which corresponds to the evaporation of water. The second stage, occurring between 110 and 205°C, mainly corresponds to the decomposition of glycerol. The decomposition of the cellulose structure in MCC mainly occupies the third stage, which occurs between 205 and 400°C and involves several steps, including dehydration, depolymerization and cleavage of glycoside units. It can be seen that the films prepared from this raw material have good thermal stability and have a wide range of application prospects.
Claims
1. A method for preparing a dense antibacterial film based on bamboo with multi-component synergistic enhancement, characterized in that: The method comprises the following steps: S1. Processing natural bamboo strips into 120 mesh bamboo powder fiber powder, referred to as BFP, and then soaking in sodium acetate buffer and then performing enzyme treatment, wherein the mass ratio of bamboo powder fiber powder to hemicellulase, laccase, and pectinase in the enzyme treatment is 100:1.5:2:1, the enzyme hydrolysis temperature is 45±5°C, the enzyme hydrolysis time is 6±1h, and after the treatment, the mixture is filtered, washed to neutrality and dried to obtain the enzyme-treated powder, referred to as E-BFP; S2. treating the powder obtained in step S1 with alkali and drying the filter residue to obtain an alkali-treated powder, referred to as A-BFP; S3. The powder A-BFP obtained in step S2 is treated by a staged bleaching method from mild to strong, and finally subjected to ultrasonic treatment, washed with boiling deionized water until neutral and dried to obtain microcrystalline cellulose, referred to as MCC; S4. Take the microcrystalline cellulose MCC obtained in step S3, add it into water to prepare a microcrystalline cellulose MCC dispersion with a mass percentage concentration of 1%, then add 10% lignin based on the mass of MCC and 15% TiO2 based on the mass of MCC to the dispersion to obtain a mixed solution, stir the mixed solution at 90±5°C for 2h to obtain a MCC / LNP / TiO2 polymer solution, then add plasticizer glycerol, referred to as G, and stir at 90±5°C for 30min to obtain a MCC / LNP / TiO2 / G polymer solution; vacuum filter it to obtain a wet sheet, and hot-press the obtained wet sheet to obtain a composite film HP-MLTG.
2. The method for preparing a bamboo-based multi-component synergistically enhanced dense antibacterial film according to claim 1, characterized in that: In step S1, the natural bamboo strips are processed into 120-mesh bamboo powder fiber powder. The specific process is to cut the natural bamboo strips into short pieces and place them in a 60°C electric blast oven to dry until the quality no longer changes. After taking them out, they are crushed by a multifunctional high-speed pulverizer, and sieved through a 120-mesh sieve to obtain a sieve-under product of 120-mesh bamboo powder fiber powder, referred to as BFP.
3. The method for preparing a bamboo-based multi-component synergistically enhanced dense antibacterial film according to claim 1, characterized in that: The step S1 is soaked in the sodium acetate buffer, wherein the sodium acetate buffer has a pH of 5.5 and a solid-liquid ratio of 1 g:20 ml.
4. The method for preparing a bamboo-based multi-component synergistically enhanced dense antibacterial film according to claim 1, characterized in that: The alkali treatment in step S2 is to place the E-BFP powder obtained in step S1 in a 3% by mass NaOH solution for 4 hours, the solid-liquid ratio is set to 1g:10ml, and the alkali treatment temperature is 80°C.
5. The method for preparing a bamboo-based multi-component synergistically enhanced dense antibacterial film according to claim 1, characterized in that: The staged bleaching method in step S3 is specifically that during the first bleaching, the ratio of the A-BFP powder obtained in step S2, sodium hydroxide, and 8 wt.% hydrogen peroxide is 1g:1g:100ml, and the subsequent bleaching uses the dried powder after the previous bleaching, sodium hydroxide, and 8 wt.% hydrogen peroxide in a ratio of 1g:1g:150ml until bleached to white. The staged bleaching method is carried out at 80±5°C.
6. The method for preparing a bamboo-based multi-component synergistically enhanced dense antibacterial film according to claim 1, characterized in that: The amount of plasticizer glycerol added in step S4 is 4% of the mass of the MCC / LNP / TiO2 polymer solution.
7. The method for preparing a bamboo-based multi-component synergistically enhanced dense antibacterial film according to claim 1, characterized in that: The hot pressing conditions in step S4 are: 100° C., 0.5 MPa in a hot press, and the hot pressing time is 40 minutes.
8. The method for preparing a bamboo-based multi-component synergistically enhanced dense antibacterial film according to claim 1, characterized in that: The method also includes placing the hot-pressed composite film HP-MLTG at 23°C and 50% relative humidity for 72 hours to balance moisture.
9. A bamboo-based multi-component synergistically reinforced dense antibacterial film prepared by the method according to any one of claims 1 to 8.
Citation Information
Patent Citations
Method for ultrasonic alkali treatment-based dual-enzyme degradation of bagasse
CN105838753A
Method for preparing nano cellulose by using natural plant fibers
CN117248386A